2020
DOI: 10.1097/md.0000000000023525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between long non-coding RNA and prognosis of patients with coronary heart disease after percutaneous coronary intervention

Abstract: Background: Long non-coding RNA (lncRNA) can predict the prognosis of patients with coronary heart disease (CHD) after obtaining percutaneous coronary intervention (PCI), while this conclusion still needs to be further confirmed. Therefore, this study attempted to explore the relationship between lncRNA and prognosis in CHD patients after PCI. Methods: The database was retrieved from China National Knowledge Infrastructure (CNKI), Chinese Biomedical literature Database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The score of fear of movement was (39.52 ± 8.63), which was at a high level, and the incidence rate of fear of movement was 52.9%. Wang Zi an et al [23] conducted a longitudinal study on patients with acute myocardial infarction after PCI. The results showed that the level of fear of movement began to increase slowly 1 week after surgery, peaked at 2 weeks after discharge, and began to gradually decrease after 2 weeks, but after 3 weeks after discharge, it has not dropped to normal levels and below for several months.…”
Section: Current Status Of Fear Of Movement In Patients With Coronary...mentioning
confidence: 99%
“…The score of fear of movement was (39.52 ± 8.63), which was at a high level, and the incidence rate of fear of movement was 52.9%. Wang Zi an et al [23] conducted a longitudinal study on patients with acute myocardial infarction after PCI. The results showed that the level of fear of movement began to increase slowly 1 week after surgery, peaked at 2 weeks after discharge, and began to gradually decrease after 2 weeks, but after 3 weeks after discharge, it has not dropped to normal levels and below for several months.…”
Section: Current Status Of Fear Of Movement In Patients With Coronary...mentioning
confidence: 99%
“…However, due to the diferent degree of coronary artery stenosis, the imaging evaluation is highly subjective, and the infuence of the degree of stenosis on the distal blood fow cannot be obtained [8,9]. In recent years, researchers have used computed tomography (CT) to reconstruct the model of coronary artery in three dimensions and computer blood fow simulation to obtain noninvasive fractional fow reserve (FFR), which has gradually deepened the application of FFR [10]. FFR is defned as the ratio of maximum blood fow at both ends of coronary artery stenosis measured in the case of vascular expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) defined as nonprotein-coding RNAs longer than 200 nucleotides [13]. Some studies verified that the abnormal expression of lncRNA in CHD [14][15][16]. Liu et al reported that lncRNA-ANRIL is expressed low in the serum of patients with CHD, and it has high predictive value both for effective treatment and for poor prognosis of them.…”
Section: Introductionmentioning
confidence: 99%